2022
DOI: 10.30865/jurikom.v9i2.4060
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Algoritma Winnowing dan Word-Level Trigrams Untuk Mengidentifikasi Kesamaan Kata

Abstract: Identifying the same words in two or more texts is the first step in the process of detecting plagiarism. Plagiarism detection software are commercially available but relatively expensive. Although some software is offered for free, the features provided are very limited. Therefore, a word similarity detection system is needed to be used as an alternative for users that can be freely accessed. The application of the pattern matching method is one of the solutions that can be used to find the similarity of word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…Winnowing is an algorithm based on a hashing approach that applies a hash function and window formation to obtain fingerprints when matching patterns. This algorithm is used by [11] based on words (word-level) still needs to be done, so this study aims to measure the level of similarity of dishes using the Winnowing algorithm and word-level trigrams. The results showed that the Winnowing algorithm applied using word-level trigrams could detect similarities in the text by 76.84%, 52.29%, 37.40%, and 19.29%.…”
Section: Introductionmentioning
confidence: 99%
“…Winnowing is an algorithm based on a hashing approach that applies a hash function and window formation to obtain fingerprints when matching patterns. This algorithm is used by [11] based on words (word-level) still needs to be done, so this study aims to measure the level of similarity of dishes using the Winnowing algorithm and word-level trigrams. The results showed that the Winnowing algorithm applied using word-level trigrams could detect similarities in the text by 76.84%, 52.29%, 37.40%, and 19.29%.…”
Section: Introductionmentioning
confidence: 99%